Application of tilt variable optical attenuator in optical amplifier to Correct stimulated raman scattering - Abdullah, Mohammad Khazani; Mahdi, Mohd. Adzir; Sheih, Shou-Jong (2009)

(untitled)
Dynamic tilt control of an optical amplifier (4) is achieved incorporating a tilt variable optical attenuator (6). This tilt variable optical attenuator (16) can dynamically adjust the tilt signal levels induced by stimulated Raman scattering in the transmission systems. The overall signal flatness can be maintained after each node that results in improvement of the wavelength division multiplexed transmission systems.